1998
DOI: 10.1002/(sici)1097-4644(19980701)70:1<110::aid-jcb11>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of naturally occurring myosin heavy chain antisense mRNA in rat heart

Abstract: Analysis of mRNA by Northern blot and reverse transcription-polymerase chain reaction demonstrated the expression of sense and considerable amounts of naturally occurring antisense mRNA for beta-myosin heavy chain (MHC) and alpha-MHC in the neonatal rat heart: antisense MHC mRNA expression of alpha-MHC and beta-MHC was approximately half of the corresponding sense MHC mRNA expression. Using a computational approach, we could identify a reverse Pol II promoter in the beta-MHC gene. Both sense and antisense MHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Furthermore, this report of the antisense expression has not linked its expression with a functional significance. More recently, Luther et al (33)(34)(35) reported the expression of antisense MHC mRNA in both the rat and human myocardium, and it was proposed that this antisense MHC regulates translation of the sense mRNA into protein. In these studies (33)(34)(35), there was no differentiation between primary transcript versus processed mature mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this report of the antisense expression has not linked its expression with a functional significance. More recently, Luther et al (33)(34)(35) reported the expression of antisense MHC mRNA in both the rat and human myocardium, and it was proposed that this antisense MHC regulates translation of the sense mRNA into protein. In these studies (33)(34)(35), there was no differentiation between primary transcript versus processed mature mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our group is focusing on natural antisense RNAs from cardiac tissues and we were previously able to isolate different antisense RNAs, including ␣ and ␤ myosin heavy chain (MyHC; Luther et al 1998) and cardiac troponin I (cTnI) antisense RNAs (Podlowski et al 2002). Our investigations with cTnI antisense RNA have so far revealed cTnI antisense-sense duplex structures in vivo and reduced protein expression with oligonucleotides directed against the sense RNA in vitro (Podlowski et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, RT was performed using the specific forward primers. We were unable to detect any ␣-MHC antisense RNA in hypothyroid or euthyroid rat hearts (12,22). However, ␤-MHC antisense RNA was present in euthyroid, and at substantially lower levels in hypothyroid, rat hearts.…”
Section: Resultsmentioning
confidence: 59%
“…To identify a mechanism for the stabilization of ␣-MHC mRNA after treatment with actinomycin D, we hypothesized that the absence of a short-lived ␣-MHC antisense RNA may account for the increased stability of ␣-MHC mRNA. To validate the RT-PCR method for antisense RNA, we found it necessary to ensure the adequacy of the denaturation of the reverse transcriptase as described in MATERIALS AND METHODS (12,22). Our findings, however, did not support this hypothesis, because we could detect no antisense ␣-MHC in ventricular myocytes.…”
Section: Discussionmentioning
confidence: 73%